Dynamics Modeling and Analysis of Split Gear Transmission System with Double Helical Gear - Ding Zhang; Geng Hu; Siyu Chen; Jinyuan Tang (Jixie chuandong)
Taking an aero-engine gearbox with split torque transmission system and double helical gears as research object. Based on the finite element node method, the model of a split torque transmission system with considering the effects of the supporting shafts and bearings, gyroscopic effect of rotor, is constructed. The time-varying meshing stiffness of double helical gear is calculated by finite element method, and the static transmission error is calculated according to the measured tooth surface. According to the established system dynamics equation, the typical modal of gear train is calculated according to the vibration theory method, and the correctness of the calculated modal is verified by the test. The time-domain and frequency-domain response is simulated with NewMark method, the time-domain response of the system is convergent and the modulation phenomenon appeared. In the frequency-domain analysis, several high and low order components of mesh frequency, shaft frequency exist. The calculated results are basically consistent with the experimental results. The study work provides a valuable reference method for the dynamic performance analysis of aeronautical gear transmission.